Liquid crystal lasers: recent advances - Schmidtke, Juergen; Lu, Lu; Kitzerow, Heinz-Siegfried; Terentjev, Eugene M. (SPIE Proceedings)

Hydrophobic gold nanoparticles via silane conjugation: chemically and thermally robust nanoparticles as dopants for nematic liquid crystals - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
We examine for the first time how chemically and thermally stable gold nanoparticles (NPs), prepared by a silane conjugation approach, affect both the thermal and the electro-optical properties of a nematic liquid crystal (LC), when doped at concentrations ranging from 0.25 to 7.5 wt%. We find that the octadecylsilane-conjugated gold NPs stabilize both the enantiotropic nematic and the monotropic smectic-A phases of the LC host with a maximum stabilization of 2 ° C for the nematic and 3.5 ° C for the smectic-A phases for the mixture containing 1 wt% of the silanized particles. The same mixture shows the lowest values for the Fréedericksz transition threshold voltage and the highest value for the dielectric anisotropy. Generally, all NP-containing mixtures, except mixtures with NP concentrations exceeding 5 wt%, reduce the threshold voltage, increase the dielectric anisotropy and reduce both rise and decay time; the latter particularly at temperatures at least 10 ° C below the isotropic–nematic phase transition on cooling.
Keywords: General Physics and Astronomy; General Engineering; General Mathematics

Microresonator-enhanced electroluminescence of an organic light emitting diode based on a columnar liquid crystal - Vollbrecht, Joachim; Kasdorf, Olga; Quiring, Viktor; Suche, Hubertus; Bock, Harald; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, Cedrik (Optics Express)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, C. (Optics Express)

Kinetics of the grating formation in holographic polymer-dispersed liquid crystals: NMR measurement of diffusion coefficients - Tang, Mingxue; Redler, Andreas; Topgaard, Daniel; Schmidt, Claudia; Kitzerow, Heinz-Siegfried (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Doping the nematic liquid crystal 5CB with milled BaTiO3nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Kitzerow, Heinz-Siegfried (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Switching performance of a polymer-stabilized antiferroelectric liquid crystal based on bent-core molecules - Atorf, B.; Hoischen, A.; Ros, M. B.; Gimeno, N.; Tschierske, C.; Dantlgraber, G.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Electrical fine tuning of liquid crystal lasers - Schmidtke, Jürgen; Jünnemann, Gisela; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Antiferroelectric gels - Strauss, J.; Kitzerow, Heinz-Siegfried (Berichte der Bunsengesellschaft für physikalische Chemie)
Keywords: General Chemical Engineering

Doping a Mixture of Two Smectogenic Liquid Crystals with Barium Titanate Nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Fernández Martínez, Manuel; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Three-dimensional structure in holographic polymer-dispersed liquid crystals - Redler, Andreas; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

New developments in nanoparticle-liquid crystal composites: from magic-sized semiconductor nanoclusters to alignment pattern formation via nanoparticle stenciling - Mirzaei, Javad; Sawatzky, Ryan; Sharma, Anshul; Urbanski, Martin; Yu, Kui; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (SPIE Proceedings)

Investigations on the director field around microdisc resonators - Urbanski, Martin; Piegdon, Karoline A.; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Liquid Crystals)

Liquid Crystal/Polymer Composites: Kinetic Study of the Grating Formation in Holographic Polymer-Dispersed Liquid Crystals - Redler, Andreas; Hoischen, Andreas; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Nanocomposites of a nematic liquid crystal doped with magic-sized CdSe quantum dots - Mirzaei, Javad; Urbanski, Martin; Yu, Kui; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Journal of Materials Chemistry)
Keywords: Materials Chemistry; General Chemistry

Electrooptic Switching in Graphene-Based Liquid Crystal Cells - Wahle, Markus; Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Liang, Yanyu; Feng, Xinliang; Müllen, Klaus (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Efficient electro-optic switching in a photonic liquid crystal fiber - Lorenz, Alexander; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)

Bold relief fabrication by means of electroconvection: basic properties of a suitable mixture - Zöller, M.A.; Stich, N.; Benning, S.A.; Hoischen, A.; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry